“Wokisme” or the French culture war - Christian Laval (Geografares, 2022)
Transcript of the author's exhibition at the GENA (Neoliberalism and Alternatives Study Group) Study Day, on May 30, 2022 at the National Conservatory of Arts and Crafts (CNAM), Paris.
Keywords: wokism; culture war; enmity; far right; neoliberalism